The streams of Gorgona Natural National Park within the global context : an introduction to the special issue (2009)
ABSTRACT: This paper highlights the importance of islands for proposing and testing hypotheses in stream ecology, and therefore, advocates for implementing reference studies in Gorgona Island (Colombian Pacific). It firstly summarizes past ecological studies in streams in Gorgona Island and outlines a series of papers resulting from a recent survey. These papers report that Gorgona Island exhibits a maritime climate, a tropical rainforest cover, and a basaltic and intrusive lithology, all typical features of islands elsewhere. They also describe that despite of the insular effect on stream biota, the proximity (< 50 km) of the island to the Pacific coast of Colombia facilitated dispersal of many faunal and floristic components from the continent, thus providing a unique opportunity for studying coastal streams in the Biogeographic Chocó. Finally, the status of Gorgona Island as a natural park established in 1984, and a relatively well known history of land uses, may further contribute to support search programs with long-term and large-scale goals.